Effect of fecal microbiota transplantation on ulcerative colitis model in rats: The gut–brain axis - Mahdis Morshedbak; Kaveh Rahimi; Mohammad Reza Tabandeh (Heliyon)
Study objectives: The impact of fecal microbiota transplantation (FMT) on the TLR4/MYD88/NF-kB signaling pathway in the colon in the ulcerative colitis model, as well as the incidence of anxiety behaviors caused by the colitis model was investigated. Methods: Twenthy four ats were induced with ulcerative colitis using a 4 % acetic acid solution administered intrarectally and were subsequently treated with prednisolone and FMT. The study examined several indicators, such as TLR4, MYD88, and NF-κB mRNA expression, along with oxidative stress factors. Additionally, it examined the relationship between anxiety-related behaviors and colitis and assessed the pro-inflammatory cytokines in the hippocampus. Results: FMT led to lower disease score index and improved colon tissue pathology findings. This was associated with reduced mRNA expression of TLR4, MYD88, and NF-κB, as well as lower levels of TOS, and higher levels of TAC, GSH, and GSSG in colon tissues. FMT was found to reduce anxiety in both the open field and elevated plus maze tests. Additionally, levels of IL-6 and TNF-a were decreased in the hippocampus. Conclusions: FMT suppressed acetic acid-induced colitis by inhibiting the TLR4/MYD88/NF-kB signaling pathway. FMT reduced anxiety in open field and plus maze tests, and resulted in decreased levels of IL-6 and TNF-a in the hippocampus.